Technological Asymmetry Among Foreign Investors and Mode of Entry - Saggi, Kamal (World Bank, Washington, D.C., 2013)
How does the preferred entry mode of foreign investors depend on their technological capability relative to that of their rivals? The authors develop a simple model of entry mode choice and evaluate its main testable implication using data on foreign investors in Eastern European countries and the successor states of the former Soviet Union. The model considers competition between two asymmetric foreign investors and captures the following tradeoffs: while a joint venture helps a foreign investor secure a better position in the product market compared with its rival, it also requires that profits be shared with the local partner. The model predicts that the efficient foreign investor is less likely to choose a joint venture and more likely to enter directly relative to the inefficient investor. The authors' empirical analysis supports this prediction: foreign investors with more sophisticated technologies and marketing skills (relative to other firms in their industry) tend to prefer direct entry to joint ventures. This empirical finding is robust to controlling for host country-specific effects and other commonly cited determinants of entry mode.